Мобільний застосунок для відстеження та бронювання вільних аудиторій в університеті - Брестовицький, P. M. (ХНУРЕ, 2020)
There are a lot of free rooms in the University in each time but students have no clue which one is currently free. For IT students, it is very important to find a place where you can comfortably perform the necessary tasks or engage in self-education. It's common knowledge, that students spend a lot of time in the in the corridors of the university. The idea is to develop mobile application and introduce it that will contain information about available rooms for selected time. For security purposes, application will have authentication associated with the university’s mail domain. If the approach has problems, the administration can detect them.